Pembinaan Akhlak Peserta Didik Melalui Pembelajaran Tahfiz Alquran - Heri Yones; Ahmad Lahmi; Aguswan Rasyid (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2022)
The reality of the changes that occur in the morals of students in this information age is something that cannot be avoided but the negative impact can be minimized through various efforts and approaches. This research aims to describe how the morals and morals of students can be fostered through the learning of Qur'anic tahfiz, the object chosen is students at the junior high school level, this is because the age generation is very vulnerable to changes that occur in their environment. Research is carried out with a qualitative approach to the type of phenomenology, which is to reveal the meaning that occurs at the research site based on existing phenomena. Data is collected through observation, interviews and documentation studies. The result of the research is that the moral development of students through the learning of Qur'anic tahfiz can be carried out smoothly, starting from tahfiz learning materials that are conditioned with moral majesty. The teacher introduced some of the moral material contained in the Qur'an. Moral coaching is also found from the approach and learning methods used by teachers, teachers apply the method of transparency, with this method students can do a direct impersonation of each exemplified by the teacher. Moral development can also be carried out through tahfiz learning media, namely the media directs students to have good morals. The limitation of this research is that researchers have not carried out tests related to the effectiveness of moral development through the Qur'anic tahfiz, therefore the space can be used as a research target for academics in the future.